Biochemistry and Occurrence of O-Demethylation in Plant Metabolism - Hagel, Jillian; Facchini, Peter (Frontiers in Physiology, 2010)
Demethylases play a pivitol role in numerous biological processes from covalent histone modification and DNA repair to specialized metabolism in plants and microorganisms. Enzymes that catalyze O- and N-demethylation include 2-oxoglutarate (2OG)/Fe(II)-dependent dioxygenases, cytochromes P450, Rieske-domain proteins and flavin adenine dinucleotide (FAD)-dependent oxidases. Proposed mechanisms for demethylation by 2OG/Fe(II)-dependent enzymes involve hydroxylation at the O- or N-linked methyl group followed by formaldehyde elimination. Members of this enzyme family catalyze a wide variety of reactions in diverse plant metabolic pathways. Recently, we showed that 2OG/Fe(II)-dependent dioxygenases catalyze the unique O-demethylation steps of morphine biosynthesis in opium poppy, which provides a rational basis for the widespread occurrence of demethylases in benzylisoquinoline alkaloid metabolism.